Interventions to reduce the negative effects of alcohol consumption in older adults: a systematic review - Roxanne Armstrong-Moore; Catherine Haighton; Nicola Davinson; Jonathan Ling (BMC, 2018)
Abstract Background Older individuals are consuming alcohol more frequently yet there is limited evidence on the effectiveness of current interventions. This systematic review aims to investigate interventions that target alcohol use in individuals aged 55 + . Methods CINAHL, ERIC, MEDLINE, Science Direct, PsychInfo, SCOPUS, Web of Science and socINDEX were searched using terms devised from the PICO (Population, Intervention, Comparison and Outcome) tool. Studies using pharmaceutical interventions, or those that investigated comorbidities or the use of other substances were excluded. Peer reviewed empirical studies written in the English language that compared the outcomes of alcohol related interventions to standard care were included in this review. Studies were appraised and assessed for quality using the relevant Critical Appraisal Skills Programme checklist. Results Seven papers were included in this review. Six were conducted in the United States of America and one in Denmark. The interventions were carried out in primary care centres and in community based groups. The studies included in this review showed varying levels of success. Participants showed improvements in at least one area of alcohol consumption or frequency of consumption however, these did not always reach significance. Conclusion Individuals in this age group appear to respond well to interventions aimed at reducing alcohol consumption. However, included studies had limitations, in particular many did not include a clear intervention description; leaving us unable to fully investigate the components required for success. Further research is needed on the effective components of alcohol interventions targeting older people.